Face Recognition using Depth Map Generation for Smart phones - Sisodhiya, Anshu; Jain, Ankita; Banakar, R M (International journal of advanced computer research, 2013)
Face recognition nowadays is one of the most popular biometric technologies because of its usability and simplicity. Face recognition that uses depth map is an emerging field, which is trying to use 2D features along with the depth information of the face for accurate identification of the subject. In this paper, a 3D face recognition system is proposed where depth information of the face is captured by calculating the deviations in the scan pattern because of the non-planarity of the face. By using this information, a depth map is generated and 3D features are extracted from it by implementing Fourier Descriptor algorithm. This 3D feature is, then, matched with the 3D features of different faces stored in the database to identify an individual.